The Analysis of Data and the Evidential Scope of Neuroimaging Results. (8th August 2017) - Wright, Jessey
Abstract: The sceptical positions philosophers have adopted with respect to neuroimaging data are based on detailed evaluations of subtraction, which is one of many data analysis techniques used with neuroimaging data. These positions are undermined when the epistemic implications of the use of a diversity of data analysis techniques are taken into account. I argue that different data analysis techniques reveal different patterns in the data. Through the use of multiple data analysis techniques, researchers can produce results that are locally robust. Thus, the epistemology of neuroimaging must take into consideration the details of the different data analysis techniques that are used to evaluate neuroimaging data, and the specific theoretical aims those techniques are deployed towards. 1 Introduction 2 Scepticism about Neuroimaging 3 Data Analysis and Evidence 4 Deconvolution and Pattern Classification Analysis 4.1 Deconvolution analysis 4.2 Region of interest selection 4.3 Pattern classification analysis 5 The Strength of Multiple Analyses 6 Conclusion